Creative Products Based on Local Wisdom Derived from Mural Paintings of Suphan Buri Province, Thailand - Netwong, Titiya; Khrouthongkhieo, Nuaon; Pijitkamnerd, Bunpod (Harmonia: Journal of Arts Research and Education, 2024)
Mural painting is a branch of fine art that reflects the excellent culture of Thailand and the development of creative products based on local resources to add value to the community. Promoting community-based tourism is implementing knowledge and findings from the study of mural paintings to be developed into creative products to create value-added local wisdom knowledge. The objectives of this research were to 1) design creative products based on local wisdom derived from mural paintings and 2) organise training and a workshop to pass on the knowledge of creating creative products based on the wisdom of the mural paintings of Suphan Buri Province, Thailand. The sample group consisted of 1) 75 people members of the community who set up murals in Suphan Buri Province, 2) five experts for evaluated product prototypes, 3) 400 tourists to satisfaction products, and 4) 22 participants for knowledge transfer. The research tools consisted of 1) The wisdom-based creative product prototype assessment form, 2. The wisdom-based creative product satisfaction questionnaire, and 3) The knowledge transfer project satisfaction assessment form. The data were analysed using mean, standard deviation, and content analysis. The research results were as follows: 1. The creative products of paper stencils framed from Wat Pratoosan and Wat No Bhuddhangkun had an overall satisfaction at a high level. The overall satisfaction was high for creative products using the 12 zodiac signs from Wat Chi Pa Khao to design and print on T-shirts. 2. The overall satisfaction in the knowledge transfer activities was at the highest level.